Cortical thickness of primary visual cortex correlates with motion deficits in periventricular leukomalacia. (22nd January 2021) - Bhat, Akshatha; Biagi, Laura; Cioni, Giovanni; Tinelli, Francesca; Morrone, M. Concetta
Abstract: Impairments of visual motion perception and, in particular, of flow motion have been consistently observed in premature and very low birth weight subjects during infancy. Flow motion information is analyzed at various cortical levels along the dorsal pathways, with information mainly provided by primary and early visual cortex (V1, V2 and V3). We investigated the cortical stage of the visual processing that underlies these motion impairments, measuring Grey Matter Volume and Cortical Thickness in 13 children with Periventricular Leukomalacia (PVL). The cortical thickness, but not the grey matter volume of area V1, correlates negatively with motion coherence sensitivity, indicating that the thinner the cortex, the better the performance among the patients. However, we did not find any such association with either the thickness or volume of area MT, MST and areas of the IPS, suggesting damage at the level of primary visual cortex or along the optic radiation. Highlights: We present evidence of a reliable correlation between Cortical Thickness of primary visual cortex and Flow Motion Sensitivity in PVL patients.